Role of α-Actinin 2 in Cytoadherence and Cytotoxicity of Trichomonas vaginalis - Lee, Hye-Yeon; Kim, Juri; Park, Soon-Jung (Journal of microbiology and biotechnology, 2017)
is a pathogen that triggers severe immune responses in hosts. α-actinin 2 (Tvα-actinin 2) has been used to diagnose trichomoniasis. Tvα-actinin 2 was dissected into three parts; the N-terminal, central, and C-terminal portions of the protein (#1, #2, and #3, respectively). Western blot of these Tvα-actinin 2 proteins with pooled patients' sera indicated that #2 and #3, but not #1, reacted with those sera. Immunofluorescence assays of two different forms of (trophozoites and amoeboid forms), using anti-Tvα-actinin 2 antibodies, showed localization of Tvα-actinin 2 close to the plasma membranes of the amoeboid form. Fractionation experiments indicated the presence of Tvα-actinin 2 in cytoplasmic, membrane, and secreted proteins of . Binding of fluorescence-labeled to vaginal epithelial cells and prostate cells was decreased in the antibody blocking experiment using anti-Tvα-actinin 2 antibodies. Pretreatment of with anti-rTvα-actinin 2 antibodies also resulted in reduction in its cytotoxicity. Flow cytometry, ligand-binding immunoblotting assay, and observation by fluorescence microscopy were used to detect the binding of recombinant Tvα-actinin 2 to human epithelial cell lines. Specifically, the truncated N-terminal portion of Tvα-actinin 2, Tvα-actinin 2 #1, was shown to bind directly to vaginal epithelial cells. These data suggest that α-actinin 2 is one of the virulence factors responsible for the pathogenesis of by serving as an adhesin to the host cells.